Keselamatan dan Kesehatan Kerja dan Lingkungan - Jeffry Yuliyanto Waisapi (Formosa Journal of Social Sciences (FJSS), 2022)
Occupational Health and Safety (K3) is a field related to the health, safety, and welfare of people working in an institution or at a project site. The purpose of implementing Occupational Safety and Health is to maintain the health and safety of the work environment, as well as protect co-workers, workers' families, consumers, and other people who may also be affected by the conditions of the work environment. Occupational Safety and Health (K3) is very important for morals, legality, and finances. All organizations have an obligation to ensure that workers and others involved remain safe at all times. In Law no. 1 of 1970 concerning Occupational Safety describes a workplace safety and health system related to the management of SMK3 which is regulated in PP 50 of 2012 concerning Occupational Health and Safety Management Systems, both managers/management, workers, integrated working environmental conditions in order to avoid and reduce accidents and occupational diseases and create a safe, efficient and effective workplace. In the same way that the analysis of the method of a job against its elements is to analyze the individual movement and time of each, or in the same way that analyzes such as aspects of a job level, responsibility and training, safety analysis also looks at the duties of the job. an operator to avoid accidents. Before completing a case study, the safety analysis should determine, the purpose of each job. If these facts are determined in advance, filter and placement, both companies and workers benefit.